Molecular Identification of Microalgae BTM 11 and its Lectin Isolation, Characterization, and Inhibition Activity - Apon Zaenal Mustopa; Rhestu Isworo; Mala Nurilmala; Dwi Susilaningsih (ANNALES BOGORIENSES, 2016)
BTM 11 is unknown species of microalgae, but has active compounds that can inhibit viruses. One of proteins produced by microalgae is a lectin. Lectin is a carbohydrate-binding protein found in various microalgae that show antiviral and antibacterial activity. The purpose of this study was to perform identification of the species of microalgae BTM 11, isolation, characterization, and assay of lectin inhibitory activity. Microalgae BTM 11 was identified to have homology with Cyanobacterium 99% and Geitlerinema sp 98%. Lectin of microalgae BTM 11 was isolated by ammonium sulfate precipitation of 75% with a molecular weight of 17 kDa. Lectin protein activity of microalgae BTM 11 was able to inhibit the enzyme activity of RNA helicase hepatitis C by 57.90% and 27.55%. In addition, the protein was able to suppress the activity of Staphylococcus aureus ATCC 6538, E. coli EPEC K.1.1. and Salmonella typhii ATCC 25241. Activitiy of lectin was stable at 30 °C and was unaffected by the action of the enzyme. These results indicate that lectin of microalgae BTM 11 could be a alternative to antiviral and antibacterial proteins.